Evaluation of a Brief, Bystander Bullying Intervention (STAC) for Ethnically Blended Middle Schools in Low-Income Communities. Issue 1 (January 2020) - Moran, Molly; Midgett, Aida; Doumas, Diana M.
We evaluated a brief, bystander bullying intervention (STAC) adapted for ethnically blended, low-income middle schools. We examined changes in bullying victimization and bias-based bullying victimization among a sample of sixth-grade students using a mixed factorial design. Students reported a significant decrease in bullying victimization and bias-based bullying victimization from baseline to a 6-week follow-up, with no differences between White students and students of color. In this article, we discuss implications for school counselors.